Peran Guru Pendidikan Agama Kristen Berdasarkan Ulangan 6 dalam Memperkuat Pendidikan Iman Keluarga Kristen Masa Kini - Reski Tandi Allo; Windi Atria Lewa; Neli Dawenan; Resviana Palungan; Asnifia Tampang (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
Faith education for children in contemporary Christian families is experiencing a crisis as many parents completely hand over the responsibility of faith education to schools and churches. This study aims to analyze the principles of faith education in Deuteronomy 6:4-9 and formulate strategic roles for Christian Religious Education teachers in empowering parents to implement faith education at home. The research method used is qualitative with a library research approach and hermeneutical analysis of Deuteronomy 6:4-9. The results show that Deuteronomy 6:4-9 emphasizes the importance of parental role modeling, repetitive teaching, integration of faith in daily life, and creation of a faith-rich home environment. Christian Religious Education teachers play a strategic role in empowering parents through theological training, provision of practical materials, continuous mentoring, partnership with churches, and exemplary living. Collaboration between Christian Religious Education teachers and families is essential to build a holistic faith education ecosystem so that children grow with a strong faith foundation from home.